Yield and nutritional composition of oyster mushrooms: an alternative nutritional source for rural people - Mostak Ahmed,; Noorlidah Abdullah,; Nuruddin, M.M. (Penerbit Universiti Kebangsaan Malaysia, 2016)
In recent decades, minimizing the frequency of nutrient deficiency and malnutrition in rural areas of developing countries becomes an alarming issue. Oyster mushrooms are rich source of both macro and micro nutrients. The objective of this paper was to evaluate the yield of newly introduced oyster mushroom strains viz. Pleurotus sajor-caju (PSC), Pleurotus flabellatus (FLB), Pleurotus florida (FLO), Pleurotus ostreatus (PO2 and PO3), Pleurotus ostreatus (HK-51) and Pleurotus geesteranus (PG1 and PG3) and to justify their nutritional values when grown in the climatic condition of Bangladesh. Strain HK-51 produced the highest amount of fresh sporophore (197.80 g). In contrast, the highest number of fruiting body was obtained from the strain FLO (82 g) followed by strain PSC (69 g). Strain PG1 has recorded the highest biological yield (278 g), productivity (55%) and biological efficiency (96%). Nutrient and mineral analysis of sporophore of strain PG1 showed protein (31.80%), lipid (3.6%), potassium (1.3 mg/100 g), phosphorus (0.8 mg/100 g), calcium (32 mg/100 g), iron (43 mg/100 g), magnesium (12 mg/100 g), copper (3.5 mcg/100 g), zinc (12.5 mcg/100 g) and manganese (2.3 mcg/100 g). This study showed that the strain PG1 performed well with regard to quality and productivity as compared to other strains. Hence, oyster mushroom strain PG1 is a potential cheap source of nutrients and minerals to combat socioeconomic problems including malnutrition, diseases linked to malnutrition, poverty reduction and agricultural diversity.